Identification of appropriate housekeeping genes for quantitative RT-PCR analysis in MDA-MB-231 and NCI-H460 human cancer cell lines under hypoxia and serum deprivation - Albuquerque, AP (2018)
Gene expression studies aimed at analyzing cancer cells under hypoxia and serum deprivation conditions show major potential for understanding molecular mechanisms associated with tumor progression as well as resistance to antitumor agents. To the best of our knowledge, a study for the identification of appropriate housekeeping genes in breast and lung cancer cells under hypoxia and serum deprivation conditions is currently missing. Given the relevance of a reliable and accurate normalization, we herein aimed to identify the appropriate housekeeping genes for breast and lung cancer cell lines cultured under hypoxia and/or serum deprivation. The stability of five commonly used housekeeping genes (ACTB, β 2M, GUSB, 18S rRNA, and PPIA) was assessed after reverse-transcription quantitative real-time PCR in MDA-MB-231 and NCI-H460 cancer cell lines using GeNorm, NormFinder and BestKeeper software. GeNorm and NormFinder ranking revealed ACTB, GUSB and PPIA as the most stable genes for both tumor cell lines. Our results support the use of ACTB/PPIA for MDA-MB-231 and GUSB/PPIA for NCI-H460 cells as the most stable combination for normalization of gene expression under hypoxic and serum deprivation conditions. Our results highlight the importance of the selection of the housekeeping genes in cancer cells subjected to different physiological stresses, such as hypoxia and serum deprivation.